Kant and the capacity to judge : sensibility and discursivity in the transcendental analytic of the Critique of pure reason - Longuenesse, Béatrice, 1950- (Princeton University Press, 2000)
Kant claims to have established his table of categories or 'pure concepts of the understanding' according to the 'guiding thread' provided by logical forms of judgement. By drawing extensively on Kant's logical writings, this book analyses this controversial claim.